Detection and Kinetics of Subgenomic Severe Acute Respiratory Syndrome Coronavirus 2 RNA Viral Load in Longitudinal Diagnostic RNA–Positive Samples . (12th February 2022) - Deming, Meagan E; Dong, Tracy Q; Agrawal, Vaidehi; Mills, Margaret G; Huang, Meei Li W; Greninger, Alexander L; Jerome, Keith R; Wener, Mark H; Paasche-Orlow, Michael K; Kissinger, Patricia; Luk, Alfred; Hoffman, Risa M; et al.
Abstract: While detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by diagnostic reverse-transcription polymerase chain reaction (RT-PCR) is highly sensitive for viral RNA, the nucleic acid amplification of subgenomic RNAs (sgRNAs) that are the product of viral replication may more accurately identify replication. We characterized the diagnostic RNA and sgRNA detection by RT-PCR from nasal swab samples collected daily by participants in postexposure prophylaxis or treatment studies for SARS-CoV-2. Among 1932 RT-PCR–positive swab samples with sgRNA tests, 40% (767) had detectable sgRNA. Above a diagnostic RNA viral load (VL) threshold of 5.1 log10 copies/mL, 96% of samples had detectable sgRNA with VLs that followed a linear trend. The trajectories of diagnostic RNA and sgRNA VLs differed, with 80% peaking on the same day but duration of sgRNA detection being shorter (8 vs 14 days). With a large sample of daily swab samples we provide comparative sgRNA kinetics and a diagnostic RNA threshold that correlates with replicating virus independent of symptoms or duration of illness. Abstract : From 2000 swab samples with severe acute respiratory syndrome coronavirus 2 detected by real-time reverse-transcription polymerase chain reaction, we comparatively analyzed subgenomic RNA kinetics, identifying a diagnostic RNA threshold (5.1 log10 copies/mL) that is independently correlated with detectable subgenomic RNA.